2013
DOI: 10.3991/ijim.v7i1.2044
|View full text |Cite
|
Sign up to set email alerts
|

Extended UTAUT to Examine the Acceptance of Web Based Training System by Public Sector

Abstract: With the development of information technology, organizations have applied e-learning system to train their employees in order to enhance the its performance. In this respect, applying web based training will enable the organization to train their employees quickly, efficiently and effectively anywhere at any time. This research aims to extend Unified Theory of Acceptance and Use Technology (UTAUT) using some factors such flexibility of web based training system, system interactivity and system enjoyment, in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…Performance expectancy was found to have a positive influence on behavioral intention (β = 0.293, t = 3.045, p < 0.01), as well as social influence (β = 0.219, t = 2.456, p < 0.05). It is consistent with previous research (Alrawashdeh & Al-Mahadeen, 2013;Cokins et al, 2020;Jaradat & Banikhaled, 2013;Le, Ngo, Trinh, & Nguyen, 2020;Park & Lee, 2021;Tarhini et al, 2016;Venkatesh et al, 2003). This study found that customers' intention to use pick-up apps depends on customers' usability and social leverage assessment.…”
Section: Discussionsupporting
confidence: 92%
“…Performance expectancy was found to have a positive influence on behavioral intention (β = 0.293, t = 3.045, p < 0.01), as well as social influence (β = 0.219, t = 2.456, p < 0.05). It is consistent with previous research (Alrawashdeh & Al-Mahadeen, 2013;Cokins et al, 2020;Jaradat & Banikhaled, 2013;Le, Ngo, Trinh, & Nguyen, 2020;Park & Lee, 2021;Tarhini et al, 2016;Venkatesh et al, 2003). This study found that customers' intention to use pick-up apps depends on customers' usability and social leverage assessment.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies based on UTAUT focus on behavioural intentions as predicted by performance expectancy, effort expectancy and social influence. Researchers also confirm facilitating conditions as it predicts use behaviour (Attuquayefio and Addo, 2014; Chang, 2013; Wong et al , 2013; Oye et al , 2012a, 2012b; Alrawashdeh and Al-Mahadeen, 2013; Nair et al , 2015; Ali and Arshad, 2016). This study also finds this to be true.…”
Section: Discussionmentioning
confidence: 90%
“…Through learners themselves and learners' interaction with the organization itself, the interactions between instructors and learners are the critical elements of the learning process (Abbad et al, 2009 ). The development of technologies used in the online learning context increases individuals' ability to interact from anywhere (Alrawashdeh and Al-Mahadeen, 2013 ). Abbad et al ( 2009 ) suggested that system interactivity indirectly impacts users' intention to use online learning systems through perceived usefulness and ease of use.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%